Successful removal of strangulating metal penile ring using a dental handpiece - Etetafia, Mabel Okiemute (BMJ Publishing Group, 2014)
BACKGROUND: Under emergency conditions, the dental handpiece can be a useful tool for removing a strangulating penile ring. OBJECTIVE: To report the successful use of a dental handpiece (dental drill) to remove a strangulating penile ring in an emergency. METHOD: A case report of a strangulating metal penile ring in a psychiatric patient who presented at the accident and emergency unit of Delta State University Teaching Hospital. RESULT: The metal ring was removed using a diamond bur in a dental handpiece. CONCLUSIONS: In case of emergency, the dental handpiece is a useful tool for removing a strangulating penile ring.